The Pursuit of Virtù - Hofstetter, Angela (Humanimalia, 2023)
The Pursuit of Virtù is a personal narrative revisiting a pivotal riding lesson that unlocked the uglier side of the adage that the horse is a mirror to your soul. The beating heart of the essay reflects on how a rider’s trauma can manifest in the body of the horse as well as how classical dressage—the pursuit of courage and collection—can provide a map to return to a harmonious state of balance that is as much mental as physical. Mostly, it is a prayer asking forgiveness from all horses who have had to carry the unbearable burden of human hearts and minds heavier than their bodies could ever be.